International experience of community support for national park development and its implications - Shuyi Kong; Mengling Xie; Wei Zhang; Chunfeng Xia; Xie Yi; Tamirat Solomon; Xinan Yin; Haifei Liu; Changhai Wang (Forestry Economics Review)
Purpose – This article aims to explore the key role of community participation in the protection and development of national parks under the global trend of national park development and provide reference for the construction of China’s national park system by analyzing international successful cases and experiences. Design/methodology/approach – The study on “International Experience of Community Support for National Park Development” integrates multimethods, from data mining reports, journals and policy docs from WB, UNEP, to case analyses. In-depth interviews with policymakers, academics and farmers reveal needs, challenges and best practices. Comparative analysis tailors findings to China’s context, offering recommendations for enhancing community support. This hybrid approach ensures practical insights for China’s application. Findings – The results of this study underscore the paramount significance of community participation as a cornerstone in advancing sustainable development and safeguarding national parks amidst a growing global awareness of environmental stewardship. Through a thorough examination of international National Parks such as Yellowstone, Maasai Mara, Uluru-Kata Tjuta and Sanjiangyuan, we reveal a blueprint of success that hinges on robust policy support, empowerment of local communities, strategic economic incentives and multifaceted cross-sectoral collaborations. In the context of domestic hurdles, including inadequate legal frameworks, narrow participation avenues and resource scarcities, our analysis outlines actionable recommendations aimed at fortifying policy and legal frameworks, establishing efficient engagement modalities, bolstering community capacity-building initiatives and fostering economic sustainability. This comprehensive approach presents a visionary roadmap for World’s national park system, guiding it towards achieving an optimal equilibrium where ecological integrity and community prosperity coexist harmoniously. Originality/value – The article underscores the originality in illuminating the pivotal role of community participation in national park protection and development amidst a global shift. By delving into international exemplars like Yellowstone, Maasai Mara, Uluru-Kata Tjuta, Sanjiangyuan and Panda, it uncovers novel insights on policy frameworks, community empowerment, economic incentives and collaborative models. This work contributes to the burgeoning discourse on balancing ecological conservation with socioeconomic development, providing a blueprint for sustainable national park management of all the world.